Physiological and health implications of a sedentary lifestyle - Tremblay, M.; Colley, R.; Saunders, T.; Healy, Genevieve; Owen, N. (N R C Research Press, 2010)
Sedentary behaviour is associated with deleterious health outcomes, which differ from those that can be attributed to a lack of moderate to vigorous physical activity. This has led to the field of "sedentary physiology", which may be considered as separate and distinct from exercise physiology. This paper gives an overview of this emerging area of research and highlights the ways that it differs from traditional exercise physiology. Definitions of key terms associated with the field of sedentary physiology and a review of the self-report and objective methods for assessing sedentary behaviour are provided. Proposed mechanisms of sedentary physiology are examined, and how they differ from those linking physical activity and health are highlighted. Evidence relating to associations of sedentary behaviours with major health outcomes and the population prevalence and correlates of sedentary behaviours are reviewed. Recommendations for future research are proposed.